2011
DOI: 10.1111/j.1558-5646.2011.01478.x
|View full text |Cite
|
Sign up to set email alerts
|

CHROMOSOMAL REARRANGEMENTS DO NOT SEEM TO AFFECT THE GENE FLOW IN HYBRID ZONES BETWEEN KARYOTYPIC RACES OF THE COMMON SHREW (SOREX ARANEUS)

Abstract: Chromosomal rearrangements are proposed to promote genetic differentiation between chromosomally differentiated taxa and therefore promote speciation. Due to their remarkable karyotypic polymorphism, the shrews of the Sorex araneus group were used to investigate the impact of chromosomal rearrangements on gene flow. Five intraspecific chromosomal hybrid zones characterized by different levels of karyotypic complexity were studied using 16 microsatellites markers. We observed low levels of genetic differentiati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
48
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 51 publications
5
48
0
Order By: Relevance
“…Conversely, divergence estimates in shrew populations differing by Rb fusions produced mixed results. In two parapatric species of shrews, molecular markers on rearranged chromosomes showed higher divergence levels than those on collinear chromosomes (Basset et al, 2006), whereas such differences were not observed among several chromosomal races of the common shrew (Horn et al, 2011). In addition to the possible lack of resolution due to the imprecise localization of the markers in shrews, these discrepancies highlight confounding difficulties in disentangling the relative contributions of reduced gene flow, ancestral polymorphism and selection at linked sites (Nachman and Payseur, 2012), particularly in closely related taxa (that is, races vs species).…”
Section: Effect Of Rb Heterozygosity On Gene Flowmentioning
confidence: 81%
“…Conversely, divergence estimates in shrew populations differing by Rb fusions produced mixed results. In two parapatric species of shrews, molecular markers on rearranged chromosomes showed higher divergence levels than those on collinear chromosomes (Basset et al, 2006), whereas such differences were not observed among several chromosomal races of the common shrew (Horn et al, 2011). In addition to the possible lack of resolution due to the imprecise localization of the markers in shrews, these discrepancies highlight confounding difficulties in disentangling the relative contributions of reduced gene flow, ancestral polymorphism and selection at linked sites (Nachman and Payseur, 2012), particularly in closely related taxa (that is, races vs species).…”
Section: Effect Of Rb Heterozygosity On Gene Flowmentioning
confidence: 81%
“…The idea of discontinuity between local populations is in good agreement with microsatellite studies. Significant population structuring of the common shrew was noted in many studies Lugon-Mouline et al, 1999Andersson, 2004;Horn et al, 2012). Magnitude of F st was not different, notably, in comparisons of samples of the same race and between different races.…”
Section: Discussionmentioning
confidence: 84%
“…According to Jiggins and Mallet (2000), bimodality is evidence of "a route to speciation" or is a witness of inhibition of gene flow between contacting forms. Also almost all authors show that intra-racial structuring is significant, and sometimes it is greater than interracial structuring (Lugon-Mouline et al, 2000;Ratkievicz et al, 2002;Horn et al, 2012). We suppose that the paradoxical results of estimations with using various kinds of frequency markers versus chromosomal diversity could be explained by a remarkable impediment of gene flow not only between races but also between populations within races.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…In the case of NovosibirskTomsk hybrid zone we would also expect strongly restricted gene flow in the proximal regions. This reduction in gene flow is probably very difficult to detect with the set of chromosomes specific microsatellite makers available at present in the common shrew [12]. More makers with known subchromosomal localisation have to be developed.…”
Section: Discussionmentioning
confidence: 99%